Analisis Maqasid Al-Shariah Terhadap Peran Pemerintah Kota Surabaya dalam Mewujudkan Kota Layak Anak - Ulya, Zakiyatul (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2020)
The research entitled: "Maqasid al-Shari'ah Analysis of the Role of the Surabaya City Government in Realizing Child Friendly Cities" is a field research that aims to answer the question how the role of the Surabaya City Government in realizing Child Friendly Cities through established public policies from the perspective of the maq??id al-shar?'ah. Research data were collected using interview and documentation techniques and then analyzed using descriptive analysis techniques with a deductive mindset. The results of the study concluded that the Surabaya City Government was very active in realizing Child Friendly Cities through the protection and fulfillment of children's rights, which was clearly seen from the existence of various public policies that were established to support institutional strengthening and fulfillment of the five Child Friendly Cities clusters.The role of the Surabaya City Government is in accordance with the concept of maqasid al-shari'ah because the determination of public policy is based on the welfare of children. This is proven by the elements of hifz al-din and hifz al-nasl in the public policy regarding civil rights and freedom, family environment, and alternative protection. In addition, there are elements of hifz al-nafs and hifz al-aql in public policies regarding institutional strengthening and the five Child Friendly Cities clusters, although they are actually less than perfect due to the absence of the hifz al-mal elements in them. [Penelitian yang berjudul: “Analisis Maqāṣid al-sharī’ah terhadap Peran Pemerintah Kota Surabaya dalam Mewujudkan Kota Layak Anak” ini merupakan penelitian lapangan (field research) yang bertujuan untuk menjawab pertanyaan bagaimana peran Pemerintah Kota Surabaya dalam mewujudkan Kota Layak Anak melalui kebijakan publik yang ditetapkan dari perspektif maqāṣid al-sharī’ah. Data penelitian dihimpun menggunakan teknik wawancara dan dokumentasi kemudian dianalisis menggunakan teknik analisis deskriptif dengan pola pikir deduktif. Hasil penelitian menyimpulkan bahwa Pemerintah Kota Surabaya sangat berperan aktif dalam mewujudkan Kota Layak Anak melalui perlindungan dan pemenuhan hak-hak anak yang terlihat jelas dari adanya berbagai kebijakan publik yang ditetapkan guna mendukung penguatan kelembagaan dan pemenuhan kelima kluster Kota Layak Anak. Peran Pemerintah Kota Surabaya telah sesuai dengan konsep maqāṣid al-sharī’ah karena penetapan kebijakan publik dilakukan berdasarkan pada kemaslahatan anak. Hal ini terbukti dengan terkandungnya unsur hifẓ al-din serta hifẓ al-nasl pada kebijakan publik mengenai hak sipil dan kebebasan serta lingkungan keluarga dan perlindungan alternatif. Selain itu, terdapat unsur hifẓ al-nafs serta hifẓ al-‘aql pada kebijakan publik mengenai penguatan kelembagaan dan kelima kluster Kota Layak Anak, meskipun sebenarnya kurang sempurna karena ketiadaan unsur hifẓ al-māl di dalamnya.]